Whole Body Scanning in Medicine: II. Clinical Aspects - Simpson, W. J. K. (1962)
Various kinds of scans were performed on 439 patients, using several types of radioactive substances. Using I(131), functioning metastases were demonstrated in 11 of 26 patients with follicular or papillary thyroid cancer; in three of these patients the results of scans were a decisive influence in attempting radioiodine therapy. Radioiron scans demonstrated extramedullary hematopoiesis in patients with polycythemia vera, myelofibrosis, and myelophthisic anemia. Radiocopper studies showed abnormal concentration in the kidneys in two patients with Wilson's disease. Radioactive strontium localized in bone metastases in at least four patients with malignant disease. Liver and kidney scans, using I(131)-Rose Bengal and Hg(203)-Neohydrin respectively, have been useful in the management of patients suffering from malignant disease, renal hypertension, and certain other disorders.